Arctic SunWest Charters (airline) -- photograph - Seale, Linda N. (2012)
Arctic SunWest Charters is based in Yellowknife and provides passenger and freight service from Yellowknife Airport and a float plane base on Great Slave Lake. Photograph taken March 2012